(untitled) (Journal of the College of Basic Education, 2023)
The locations of the seasonal market fi baild alhijaz for the Arabs before Islam were theaters for the advancement of aspects of thought and literature. With the passage of time, the unified Arab language appeared, Standard Arabic, in which the Noble Qur’an was revealed.